Rotavirus vaccination and the risk of type 1 diabetes and celiac disease: A systematic review and meta-analysis - Zhang, Xue; Xu, Xiang-fei; Jin, Jie (Frontiers in Pediatrics, 2022)
Background Rotavirus vaccination has been proven to effectively protect against rotavirus gastroenteritis. However, there are concerns about the relationship between rotavirus vaccination and the risk of autoimmune disorders. Thus, we conducted a systematic review and meta-analysis to comprehensively assess the association between rotavirus vaccination and type 1 diabetes (T1D) or celiac disease (CD) risk. Methods A systematic review and meta-analysis were conducted to evaluate the type 1 diabetes or celiac disease associated with rotavirus vaccination. The following journal databases were searched to identify potential studies for inclusion: PubMed, Embase, and Cochrane Library databases. Results Seven articles involving more than 5,793,055 children were included. Our results showed that rotavirus vaccination does not alter the subsequent risk of T1D (RR 0.94, 95% CI: 0.82–1.09) or CD (RR 0.86, 95% CI: 0.64–1.17) after vaccination. Furthermore, the risk of T1D was not increased or decreased for children fully exposed to rotavirus vaccination (RR 0.86, 95% CI, 0.54–1.36) and for children partially exposed to rotavirus vaccination (RR 1.05, 95% CI, 0.87–1.26). However, younger (<5 years) vaccinated children at the end of study (RR 0.84, 95% CI = 0.75–0.95) may be at a lower risk for T1D than older (≥5 years) vaccinated children (RR 0.93, 95% CI, 0.81–1.07). Conclusion The findings of this study suggest that rotavirus vaccination does not appear to be associated with T1D or CD in children. The protective effect of rotavirus vaccination on T1D may be presented by time dependent.